Synergy of Financial Literacy and Financial Inclusion in Nepal - Chand, Mahendra Bahadur; K.C., Subin; Katuwal, Khagendra (Nepalese Journal of Economic Studies, 2025)
This paper explores the synergy between financial literacy and financial inclusion in Nepal using a quantitative approach based on baseline survey data from the Nepal Rastra Bank. The investigation focuses on three key components: financial knowledge, attitude, and behavior, analyzed through descriptive and multiple regression techniques. Financial literacy is treated as the independent variable and financial inclusion as the dependent variable, with demographic factors as controls. The Ordinary Least Squares (OLS) regression analysis reveals a significant positive relationship; specifically, a one-unit increase in financial literacy correlates with a 0.215-unit increase in financial inclusion, reducing to 0.161 units when controlling for demographic variables. Notably, formal employment participation enhances financial inclusion by 0.527 units, and higher education levels are positively associated with financial inclusion. These findings highlight the critical role of financial literacy in fostering financial inclusion emphasizing the need for targeted interventions to strengthen financial literacy. JEL Classification: G53, G20, O16, C50